Способ прогнозирования износостойкости твердосплавных режущих инструментов - Нестеренко В. П. Владимир Петрович; Арефьев К. П. Константин Петрович; Кучко Г. Д. Галина Дмитриевна; Лычагин Д. В. Дмитрий Васильевич; Николаева В. П. Валентина Петровна
опубл. 27.05.09